EVALUATION OF BILEVEL NONINVASIVE VENTILATION AGAINST CONVENTIONAL OXYGEN THERAPY IN THE TREATMENT OF ACUTE CARDIOGENIC PULMONARY EDEMA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute cardiogenic pulmonary edema (ACPE) is a life-threatening emergency associated with acute respiratory failure and significant mortality. Non-invasive ventilation, particularly bilevel positive airway pressure (BiPAP), has emerged as an effective alternative to conventional oxygen therapy (COT) in improving oxygenation and reducing respiratory distress. This study aimed to compare the efficacy and safety of BiPAP with conventional oxygen therapy in the management of ACPE. Methodology: This prospective randomized comparative study included 100 patients diagnosed with ACPE admitted to the emergency department. Patients were randomly divided into two groups: Group I received BiPAP along with standard anti-failure treatment, while Group II received conventional face mask oxygen therapy with anti-failure measures. Clinical examination, arterial blood gas analysis, electrocardiography, echocardiography, APACHE II scoring, and laboratory investigations were performed in all patients. Statistical analysis was conducted using SPSS version 25.0, and p